The Problems of Pesantren Education in Improving Human Academic Quality in the Global-Multicultural Era - Ani Aryati; Qolbi Khoiri (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
This scientific work outlines the obstacles facing Pesantren education in improving academic human beings' global-multicultural era. Pesantren global currents can cause paradox or symptoms of counter-morality. So does the pattern of life in the West, even significantly affect the moral decay, moral and human behavior. With this condition, the influence is considerable on human life, both physical and spiritual. Thus, Pesantren education faced various challenges with developing education models in the era of globalization implemented by community members, such as system problems, human resource problems, and curriculum development. Therefore, to improve the quality of academic humanity in the global-multicultural era, Pesantren have problems exploring all the resources they have. Because Pesantren education is less concerned with the situation, human resource problem, a strong influence of western culture in domination and imperialization of information, and the current culture of globalization can lead to paradox or symptoms of counter-morality. With this problem, a Pesantren can devote all the power, effort, and ability to innovate. Finding something new can help a student's life for the better. However, if Pesantren does not dig all his skills, he will be left behind by the ever-evolving era.